Evolution of Land Cover and Ecosystem Services in the Frame of Pastoral Functional Categories: A Case Study in Swedish Lapland - Courault, Romain; Cohen, Marianne (Sustainability, 2020)
International audience Ecosystem services (ES) are a key-component for sustainable management of human-environment systems, particularly in polar environments where effects of global changes are stronger. Taking local knowledge into account allows the valuation of ES experienced by stakeholders. It is the case for reindeer herders in Scandinavia, the ungulate being a keystone specie for subarctic socio-ecosystems. We adapt the ecosystem services assessment (ESA) proposed in Finland to the case study of the Gabna herders' community (Sweden), considering its cultural, geographical, and dynamic specificities. We used Saami ecological categories over the land-use categories of the CORINE Land Cover (CLC). We reassessed ES at the scale of the Gabna community and its seasonal pastures. We studied their evolution over 2000-2018, using CLC maps and Change CLC maps. Integration of Saami ecological categories in the classification of land cover did not substantially change the land cover distributions. However, ES were greater in Saami land use compared to other CLC categories. Cultural services were higher for summer and interseasonal pastures, dedicated to the reindeer reproduction, suggesting interactions between provisioning and cultural ES. Land cover changes are mostly represented by intensive forestry (5% of winter pastures) impeding reindeer grazing activity, while other seasonal pasture landscape composition stayed comparable along time. Consequently, forest activity, and in a lesser extent glacier melting and urbanization are the main drivers of the temporal evolution of ES. In the frame of pastoral landscapes conservation, the use of local terminologies opens perspectives for a holistic approach in environmental science. It raises the importance of local stakeholders as co-researchers in nature conservation studies.